DIPLOMASI PUBLIK BARU DALAM PENGENALAN BAHASA DAN BUDAYA JEPANG DI INDONESIA: STUDI TERHADAP KANAL YOUTUBE NIHONGO MANTAPPU - Habib Ali Zainal Abidin (2023)
This research aims to provide analysis results related to the characteristics of new public diplomacy that emerged in the process of introducing the Japanese language and culture in Indonesia through Nihongo Mantappu's Youtube channel by using the theory of globalization and cross-cultural communication as well as the theory of new public diplomacy as an analytical tool. The method used in this study is descriptive qualitative, which aims to explore and know deeply the meaning related to the characteristics of new public diplomacy that appears on Nihongo Mantappu's Youtube channel. Data sources in this study are divided into primary and secondary data sources obtained through direct interviews with actors and academics related to and based on observations of various documents and audiovisual materials. The final results of this research show that eight characteristics of new public diplomacy later appeared on Nihongo Mantappu's Youtube channel in the process of introducing the Japanese language and culture in Indonesia, namely: the active role of non-state actors, the use of Youtube as a tool in new public diplomacy, interactive and sustainable relationship building, networking as a source of approach, horizontal relations, Japan's national branding in Indonesia, the blurring of media boundaries, and maintaining the international environment between Japan and Indonesia.